Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 9 - Section 9.3 - The Parabola - Exercise Set - Page 999: 107



Work Step by Step

Comparing the given equation with the standard form, we have $A=3, B=-2\sqrt 3, C=1$ Thus $B^2-4AC=(-2\sqrt 3)^2-4(3)(1)=12-12=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.